Human rhinoviruses enter and induce proliferation of B lymphocytes. Issue 2 (8th June 2016) - Aab, A.; Wirz, O.; van de Veen, W.; Söllner, S.; Stanic, B.; Rückert, B.; Aniscenko, J.; Edwards, M. R.; Johnston, S. L.; Papadopoulos, N. G.; Rebane, A.; Akdis, C. A.; et al.
Abstract: Background: Human rhinoviruses (HRVs) are one of the main causes of virus‐induced asthma exacerbations. Infiltration of B lymphocytes into the subepithelial tissue of the lungs has been demonstrated during rhinovirus infection in allergic individuals. However, the mechanisms through which HRVs modulate the immune responses of monocytes and lymphocytes are not yet well described. Objective: To study the dynamics of virus uptake by monocytes and lymphocytes, and the ability of HRVs to induce the activation of in vitro ‐cultured human peripheral blood mononuclear cells. Methods: Flow cytometry was used for the enumeration and characterization of lymphocytes. Proliferation was estimated using 3 H‐thymidine or CFSE labeling and ICAM‐1 blocking. We used bead‐based multiplex assays and quantitative PCR for cytokine quantification. HRV accumulation and replication inside the B lymphocytes was detected by a combination of in situ hybridization (ISH), immunofluorescence, and PCR for positive‐strand and negative‐strand viral RNA. Cell images were acquired with imaging flow cytometry. Results: By means of imaging flow cytometry, we demonstrate a strong and quick binding of HRV types 16 and 1B to monocytes, and slower interaction of these HRVs with CD4+ T cells, CD8+ T cells, and CD19+ B cells. Importantly, we show that HRVs induce the proliferation of B cells, while the addition of anti‐ICAM‐1 antibody partially reduces this proliferation for HRV16. We prove with ISH that HRVs can enter B cells, form their viral replication centers, and the newly formed virions are able to infect HeLa cells. In addition, we demonstrate that similar to epithelial cells, HRVs induce the production of pro‐inflammatory cytokines in PBMCs. Conclusion: Our results demonstrate for the first time that HRVs enter and form viral replication centers in B lymphocytes and induce the proliferation of B cells. Newly formed virions have the capacity to infect other cells (HeLa). These findings indicate that the regulation of human rhinovirus‐induced B‐cell responses could be a novel approach to develop therapeutics to treat the virus‐induced exacerbation of asthma.